1998
DOI: 10.1080/758524403
|View full text |Cite
|
Sign up to set email alerts
|

Baseball success and the structure of salaries

Abstract: The purpose of this research is to examine some competing assumptions regarding the hiring behaviour of major league baseball clubs. One hypothesis is that owners and general managers of teams enter the free agent market with a view to attracting the best talent available in order to win games. We might refer to this as the 'win games' strategy. A potentially alternative view is that they compete in this market for marquee players who will attract paying customers to the ball park. We can refer to this as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 3 publications
1
21
0
1
Order By: Relevance
“…11. For professional baseball teams, see Bloom (1999), DeBrock et al (2001), Depken (2000), Harder (1992) or Richards and Guell (1998). For soccer and hockey teams, see respectively Lehmann and Wacker (2000) and Gomez (2002).…”
Section: Previous Resultsmentioning
confidence: 99%
“…11. For professional baseball teams, see Bloom (1999), DeBrock et al (2001), Depken (2000), Harder (1992) or Richards and Guell (1998). For soccer and hockey teams, see respectively Lehmann and Wacker (2000) and Gomez (2002).…”
Section: Previous Resultsmentioning
confidence: 99%
“…Using data from the US National Basketball League, Berri (2001) shows that an increase in payroll inequality within a team actually leads to an increase in wins. Richards and Guell (1998) give evidence that MLB teams with greater salary variance have lower winning percentages and that salary dispersion seems to have no effect on the probability of winning championships. Bloom (1999) tests whether increases in salary dispersion within MLB teams have a positive or a negative effect on performance.…”
Section: Introductionmentioning
confidence: 91%
“…The salary distribution among players and its impact on performance is an active and large area of research in professional team sports. For example, Richards and Guell (1998) found that the variance of the team's salary distribution is negatively correlated with winning percentage for MLB, while controlling for lagged winning percentage and total payroll. Bloom (1999), Depken (2000), Debrock, Hendricks, and Koenker (2004) and Jewell and Molina (2004) all found a negative impact of dispersion in MLB.…”
Section: A Impact Of Salary Distribution On Team Performancementioning
confidence: 99%